Outcome of Disseminated Intravascular Coagulation in Relation to the Score when Treatment was Begun - Wada, Hideo; Wakita, Yoshihiro; Nakase, Tutomu; Shimura, Minori; Hiyoyama, Katsuyo; Nagaya, Shousaburou; Mori, Yoshitaka; Shiku, Hiroshi; the Mie DIC study group (Thrombosis and Haemostasis, 1995)
We examined 395 patients with disseminated intravascular coagulation (DIC) divided into two groups: non-leukemic and leukemic. In 58% of the patients as a whole, treatment of DIC resulted in complete or partial remission, while exacerbation and death occurred in 31%. The efficacy of DIC treatment in the non-leukemic group was less than that in the leukemic group, indicating that the outcome of DIC depended, in part, on the underlying disease. We examined hemostatic indicators in relation to DIC score: prothrombin time (PT) ratio, FDP, platelet count, and fibrinogen levels were found to be important indicators for the diagnosis of DIC, but not for Pre-DIC. Plasma levels of fibrin-D-dimer, thrombin-antithrombin complex (TAT), and plasmin- plasmin inhibitor complex (PPIC) were significantly increased in pre-DIC. The efficacy of treatment in relation to the DIC score when the treatment was begun showed that greater efficacy was achieved in pre-DIC than in DIC patients. The outcome was poorer with increasing DIC score, suggesting that early diagnosis and early treatment are important. On examining the relationship between outcome and hemostatic indicators, we found that the PT ratio and the levels of antithrombin, plasminogen, PPIC, the PPIC/TAT ratio, and thrombomodulin were related to outcome, suggesting that very high consumption of blood coagulation factors, liver dysfunction, hypofibrinolysis, or organ failure caused a poor outcome. Although the outcome in DIC patients may not depend substantially on plasma levels of TAT and fibrin-D- dimer, we can use these indicators to treat DIC patients at an early stage.